Realización de proyectos de vida en las organizaciones sensibles, coherentes y lucidas - Meza Álvarez, Joaquín Javier; Bejarano Garzón, Lilian Astrid (Ingeniería, 1999)
This anide is designed to prepare managers, for dealing successfully with callenges posed by an increasingly competitive and time-responsive marketplace, and also in prepare them to improve social relationships between internal customers and their full plane life realitation wich gives a strong managers thinking globally and act locally in all levels, always aware of their impact on corporate effectiveness and competitiveness.